An Experimental Investigation into the Difference in the External Noise Behavior of a High-Speed Train between Viaduct and Embankment Sections. (29th March 2022) - Li, Muxiao; Deng, Tiesong; Wang, Di; Xu, Fan; Xiao, Xinbiao; Sheng, Xiaozhen
Abstract : Track construction is likely to exert a significant effect on railway environmental noise. In this study, a detailed comparative investigation was conducted to analyze the differences in the external noises generated by a Chinese high-speed train passing through typical lines at different speeds. Acoustic experiments were conducted on both viaduct and embankment sections by using a microphone array having 78 channels, to distinguish the effects of two types of track structures on the sound fields around these, identify the sources, and determine the contribution and distribution of each part of the train. The quantized sound power contribution of each region on the train surface determined using the identification results obtained from the experiments and analysis shows that the main noise sources of the train are located in three regions: the lower parts, bogie, and train body. The pantograph was the dominant noise source at speeds above 300 km/h. Considering the embankment as a reflective surface compared with the viaduct, the ground reflection effect results in a higher sound power level in the embankment section. Furthermore, the largest difference between the two sections increases to 1.8 dB at a speed of 350 km/h. In addition, the reflection effect is more apparent at high speeds, and the reflection is evident in the low-frequency band (<1000 Hz). The analysis of the experimental results is effective for identifying the difference and satisfies the requirement for reducing external pass-by noise in typical operational lines.